2020
DOI: 10.1101/2020.07.28.225102
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyronaridine and artesunate are potential antiviral drugs against COVID-19 and influenza

Abstract: Since the first human case was reported in Wuhan Province, China in December 2019, SARS-CoV-2 has caused millions of human infections in more than 200 countries worldwide with an approximately 4.01% case-fatality rate (as of 27 July, 2020; based on a WHO situation report), and COVID-19 pandemic has paralyzed our global community. Even though a few candidate drugs, such as remdesivir (a broad antiviral prodrug) and hydroxychloroquine, have been investigated in human clinical trials, their therapeutic efficacy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…A recent report showed that a number of artemisinin-related compounds have some anti-SARS-CoV-2 activity, with dihydroartemisinin, artesunate, and arteannuin B having IC 50 values <30 μM (Cao et al 2020), and dihydroartemisinin ACTs with 1-10 μM IC 50 s (Bae et al 2020). Artesunate was reported to have IC 50 values against SARS-CoV-2 of 7-12 μg/mL (0.7-1.2 μM; Gilmore et al 2020) and 2.6 μM (Bae et al 2020). Knowing that artemisinin is much more bioavailable per os when delivered via A. annua (Weathers et al 2011; Weathers et al 2014; Desrosiers et al 2020), we posited that encapsulated powdered dried leaves of A. annua may be a safe, cost-effective therapeutic to combat SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report showed that a number of artemisinin-related compounds have some anti-SARS-CoV-2 activity, with dihydroartemisinin, artesunate, and arteannuin B having IC 50 values <30 μM (Cao et al 2020), and dihydroartemisinin ACTs with 1-10 μM IC 50 s (Bae et al 2020). Artesunate was reported to have IC 50 values against SARS-CoV-2 of 7-12 μg/mL (0.7-1.2 μM; Gilmore et al 2020) and 2.6 μM (Bae et al 2020). Knowing that artemisinin is much more bioavailable per os when delivered via A. annua (Weathers et al 2011; Weathers et al 2014; Desrosiers et al 2020), we posited that encapsulated powdered dried leaves of A. annua may be a safe, cost-effective therapeutic to combat SARS-CoV-2 infections.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin also blunts fibrosis (Larson et al 2019; Dolivo et al 2020), another problem experienced by SARS-CoV-2 survivors that causes more lasting damage to organs (Lechowicz et al 2020; Liu et al 2020a). A recent report showed that a number of artemisinin-related compounds have some anti-SARS-CoV-2 activity, with dihydroartemisinin, artesunate, and arteannuin B having IC 50 values <30 μM (Cao et al 2020), and dihydroartemisinin ACTs having 1-10 μM IC 50 values (Bae et al 2020). Artesunate was reported to have IC 50 values against SARS-CoV-2 of 7-12 μg/mL (0.7-1.2 μM; Gilmore et al 2020) and 2.6 μM (Bae et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we examined two sets of cationic compounds that have been recently proposed as potential COVID-19 therapeutics based on either in vitro activity against SARS-CoV-2 or published activity against other related viruses (Baker et al, 2020;Gawriljuk et al, 2020;Puhl et al, 2020;, as potential inhibitors of the primary transporters involved in the renal and hepatic secretion of organic cations, i.e., OCT1, OCT2, MATE1 and MATE2-K. The first set consisted of five antiparasitic/antimalarial compounds proposed to exhibit antiviral activity: chloroquine, hydroxychloroquine, and quinacrine (proposed to inhibit SARS-CoV-2 activity; (Uzunova et al, 2020;Pineda et al, 2021); and tilorone and pyronaridine (proposed to inhibit SARS-CoV-2 activity and investigated against activity of other viral infections, including Ebola, Chikungunya virus and other Coronavirus-caused diseases such as Middle Eastern Respiratory Syndrome Coronavirus (MERS-CoV) MARV; (Bae et al, 2020;Ekins and Madrid, 2020;Lane and Ekins, 2020;Puhl et al, 2020). The second set of molecules consisted of the widely accessible, over the counter antiseptic molecules cetylpyridinium (frequently used in mouthwash) and miramistin (which is available in Russia), both of which display broad-spectrum antiviral activities that have garnered attention for their potential use in COVID-19 treatment (Mukherjee et al, 2017;Baker et al, 2020;Osmanov et al, 2020;Vergara-Buenaventura and Castro-Ruiz, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Artesunate-amodiaquine (AS-AQ), is also an antimalarial drug. Bae et al suggested that it is highly effective against COVID-19 infection that develops in human lung epithelial cells (52). Berberine, an isoquinoline alkaloid, inhibits DNA synthesis and reverse transcriptase activity.…”
Section: Irnmf Identified Of Potential Drug For Covid-19mentioning
confidence: 99%